2010
DOI: 10.1192/bjp.bp.109.076489
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life of people with schizophrenia, bipolar disorder and other psychotic disorders

Abstract: Depressive symptoms are the strongest predictors of poor QoL/HRQoL in psychotic disorders. Subjective loss of QoL associated with psychotic disorders may be smaller than objective loss of functioning suggests. The EQ-5D is problematic as an outcome measure in psychotic disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
138
3
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 202 publications
(155 citation statements)
references
References 50 publications
12
138
3
2
Order By: Relevance
“…To date methodologically rigorous research has failed to evidence the effectiveness of CBTp for treating depression in psychosis (Wykes et al, 2008). This is all the more concerning in light of Saarni et al's (2010) finding that depressive symptoms are the strongest predictors of poor quality of life in psychotic disorders. Previous research has shown that ACT can reduce levels of depression in non-psychotic populations (Zettle & Hayes, 1986;Petersen, 2007).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…To date methodologically rigorous research has failed to evidence the effectiveness of CBTp for treating depression in psychosis (Wykes et al, 2008). This is all the more concerning in light of Saarni et al's (2010) finding that depressive symptoms are the strongest predictors of poor quality of life in psychotic disorders. Previous research has shown that ACT can reduce levels of depression in non-psychotic populations (Zettle & Hayes, 1986;Petersen, 2007).…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Schizophrenia and bipolar disorder are characterized by chronic, and sometimes relapsing and remitting courses that impact negatively on the premorbid functioning and quality of life of sufferers (Harding et al, 1987;Rietschel et al, 2009;Saarni et al, 2010;Latalova et al, 2011;Aloba et al, 2013). The use of medications, in conjunction with other psychosocial interventions constitutes the cornerstone in the management of these disorders (Barnes et al, 2011;Goodwin et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In a Finnish study with a large sample size, it is reported that schizoaffective disorder had the lowest HRQOL, followed by BD-I and schizophrenia, which showed comparable losses of HRQOL assessed with EQ-5D (16). In another study, it was found that patients with BD or schizophrenia when in remission had similarly poor HRQOL levels in all four domains of the WHOQOL-BREF (17).…”
Section: Hrqol In Bd Compared To Hrqol In Other Psychiatric Disordersmentioning
confidence: 82%